Scalp-Sparing Radiation With Concurrent Temozolomide and Tumor Treating Fields (SPARE) for Patients With Newly Diagnosed Glioblastoma - Miller, Ryan; Song, Andrew; Ali, Ayesha; Niazi, Muneeb; Bar-Ad, Voichita; Martinez, Nina; Glass, Jon; Alnahhas, Iyad; Andrews, David; Judy, Kevin; Evans, James; Farrell, Christopher; et al. (Frontiers in Oncology, 2022)
Introduction Standard-of-care treatment for patients with newly diagnosed glioblastoma (GBM) after surgery or biopsy includes concurrent chemoradiation followed by maintenance temozolomide (TMZ) with Tumor Treating Fields (TTFields). Preclinical studies suggest TTFields and radiotherapy work synergistically. We report the results of our trial evaluating safety of TTFields used concurrently with chemoradiation. Methods This is a single-arm pilot study. Adult patients (age ≥ 18 years) with newly diagnosed glioblastoma and a Karnofsky performance score (KPS) of ≥ 60 were eligible. All patients received concurrent scalp-sparing radiation (60 Gy in 30 fractions) with TMZ (75 mg/m2 daily) and TTFields (200 kHz). Maintenance therapy included TMZ and continuation of TTFields. Scalp-sparing radiation treatment was used to reduce radiation dermatitis. Radiation treatment was delivered through the TTFields arrays. The primary endpoint was safety and toxicity of tri-modality treatment within 30 days of completion of chemoradiation treatment. Results 30 patients were enrolled, including 20 (66.7%) males and 10 (33.3%) females, with a median age of 58 years (range 19 to 77 years). Median KPS was 90 (range 70 to 100). 12 (40%) patients received a gross total resection. 12 (40%) patients had multifocal disease at presentation. 20 (66.7%) patients had unmethylated O(6)-methylguanine-DNA-methyltransferase (MGMT) promotor status. Median follow-up was 15.2 months (range 1.7 to 23.6 months). Skin adverse events were noted in 83.3% of patients, however, these were limited to Grade 1 or 2 events, which resolved spontaneously or with topical medications. The primary end point was met; no TTFields discontinuation occurred during the evaluation period due to high grade scalp toxicity. A total of 27 (90%) patients had progression, with a median progression-free survival (PFS) of 9.3 months (95% confidence interval (CI): 8.5-11.6 months). The 1-year progression-free survival was 23% (95% CI: 12%-45%). The median overall survival (OS) was 15.8 months (95% CI: 12.5 months-infinity). The 1-year overall survival was 66% (95% CI: 51%-86%). Conclusions Concurrent TTFields with scalp-sparing chemoradiation is a feasible and well tolerated treatment option with limited toxicity. A phase 3, randomized clinical trial (EF-32, clinicaltrials.gov Identifier: NCT04471844) investigating the clinical benefit of concurrent TTFields with chemoradiation treatment is currently enrolling.